2011
DOI: 10.5194/npg-18-829-2011
|View full text |Cite
|
Sign up to set email alerts
|

Scaling properties of pH fluctuations in coastal waters of the English Channel: pH as a turbulent active scalar

Abstract: Abstract. We consider here pH and temperature fluctuations in marine waters, recorded at fixed points using high resolution automatic devices. We analyze time series coming from 4 monitoring stations located along French coast: one station is situated in the coastal area off Boulogne-sur-mer (Eastern English Channel) and 3 stations in the Bay of Seine. All these pH time series reveal large fluctuations at all scales similar to turbulent temperature fluctuations. We compare the pH and temperature time series th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, the impossibility of a time‐varying analysis does not permit assessment of the variability of the relative contributions of forcings with time. In addition, the method is not able to document multiannual variability due to the lack of significant variability at time scales greater than 1 yr. Alternatively, the power law behavior ( Etrue(ftrue)fβ) of the spectrum trend gives scaling properties of variables (Schmitt et al ; Zongo and Schmitt ; Derot et al ). The scaling exponent β is equal to 0 for noise, 2 for Brownian motion and 5/3 for turbulence (Huang et al ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the impossibility of a time‐varying analysis does not permit assessment of the variability of the relative contributions of forcings with time. In addition, the method is not able to document multiannual variability due to the lack of significant variability at time scales greater than 1 yr. Alternatively, the power law behavior ( Etrue(ftrue)fβ) of the spectrum trend gives scaling properties of variables (Schmitt et al ; Zongo and Schmitt ; Derot et al ). The scaling exponent β is equal to 0 for noise, 2 for Brownian motion and 5/3 for turbulence (Huang et al ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the measurement of the photosynthetically active radiation (P.A.R) parameter is an exception and for obvious reasons, the sensor is not installed in the tube, but on the top of the sea wall. Each parameter is recorded at a frequency of 20 minutes, except for the three nutrient parameters (nitrates, silicates, and phosphates) which are recorded with a periodicity of 12 hours (Dur et al 2007;Derot et al 2015;Zongo and Schmitt 2011;Huang and Schmitt 2014). Table 1 lists all the parameters that were used in our study.…”
Section: Marel Carnot Datamentioning
confidence: 99%
“…The anti-correlation between temperature and oxygen showed that higher temperatures may favor larger phytoplankton growth rate, and hence, with a time delay, a lower percentage of oxygen (Huang & Schmitt, 2014). In addition, Zongo & Schmitt, (2011) demonstrated that pH fluctuations in marine waters are strongly influenced by turbulent hydrodynamical transport, and may be considered as a turbulent active scalar (Zongo & Schmitt, 2011).…”
Section: Resultsmentioning
confidence: 99%